Preparation and characterization of soluble dietary fiber from tiger nut residues, showing enhanced antioxidant activity and metal-ion-binding properties - Wang, Weihao; Quan, Zhigang; Kou, Fang; Zhang, Shenglong; Cao, Longkui; Zhang, Zhi (Frontiers in Nutrition, 2023)
To improve the utilization of soluble dietary fiber (SDF) from tiger nut residues, the response surface methodology was used to optimize the conditions of superfine grinding to produce SDF with antioxidant and metal-ion-binding properties. The yield was increased (30.56%) and the average particle diameter of SDF was decreased (D50: 32.80 μm) under the optimal conditions (a proportion of grinding medium of 100%, a feeding mass of 0.90 kg, a grinding time of 20 min, and a moisture content of 8.00%). In addition, superfine grinding substantially modified the surface morphology and increased the SDF content and the proportion of monosaccharides by decreasing the molecular weight. Moreover, superfine grinding remarkably enhanced the in vitro antioxidant activities (ABTS+, DPPḤ, and ·OH) of the SDF, which also exhibited favorable metal-ion-binding properties (Ca2+, Zn2+, and Co2+). These results suggest that superfine grinding can be used as a technique to modify dietary fiber to manufacture functional SDF.